Adhesive built-up edge on tool steels due to friction and wear - O.M. Makovkin; O.V. Dykha; I.K. Valchuk (Проблеми трибології)
When processing metals by cutting, there are a number of materials prone to growth. This phenomenon leads to a change in the geometry of the cutter, cutting forces and surface quality, final dimensions of the part. In friction nodes: shaft-sleeve, piston-sleeve, etc. this phenomenon causes jamming. In this work, experimental studies of the processes of dry friction of tool steels with coatings were carried out to evaluate the effectiveness of reducing the growth process. As a result, it was established that the nature of formation, destruction and size of growth of materials prone to growth depends on the chemical composition of the material and modes of friction. High-strength chromium-manganese steels are most prone to growth and microseizures. It is shown that the well-known recommendation of increasing speed cannot always be used to prevent build-up, but it can be achieved by using single-layer and multi-layer coatings with a defect-free structure and moderate friction modes. It was found that electrolytic single-layer nickel and chromium coatings contribute to the formation of growth on the studied materials and this phenomenon does not depend on the modes of friction, while the same chemical coatings, which have an almost defect-free structure, are almost not prone to growth formation.